(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The application of SBS polymer (styrene butadiene styrene) to the mixture to improve the performance results in necessary high temperatures that negatively impact the characteristics of the mixture modified with SBS. The purpose of the study is to forecast models for the compaction temperature and mixing temperature of the mixtures that modifying with SBS and evaluates the impact of filler kind, asphalt content and styrene butadiene styrene content on the temperatures. (3%, 4%and 5%) of the asphalt’s weight cement is produced of styrene butadiene styrene and asphalt cement grade (40-50). Asphalt mixtures were tested using two methods: compaction of asphalt mixture test and mix coating test. According to the outcomes of experimental testing, there is a negative association between the asphalt content and the mixing and the compaction temperatures. However, there is a positive association between the content of SBS and the mixing and compaction temperatures. The modified asphalt blend containing lime stone dust has produced high mixing temperature and compaction temperature than the mixture containing Portland cement. In HSRV-O approach the compaction and mixing temperatures of modified bitumen with styrene butadiene styrene decreased in contrast to the super pave method while HSRV-E method showed even greeter decreases.